Synthesis, characterization, and evaluation of copper-doped zinc oxide nanoparticles anticancer effects: in vitro and in vivo experiments - Habib Ghaznavi; Mohammad Reza Hajinezhad; Zahra Hesari; Milad Shirvaliloo; Saman Sargazi; Sheida Shahraki; Eshagh Ali Saberi; Roghayeh Sheervalilou; Somayeh Jafarinejad (BMC Cancer)
Abstract Background and aim Zinc oxide and copper oxide nanoparticles are known for their promising biological activities. This study aims to synthesize zinc oxide nanoparticles and copper-doped zinc oxide nanoparticles to harness the combined cytotoxic and anticancer effects of them in vitro and in vivo studies. Methods Zinc oxide nanoparticles, both doped and undoped, were synthesized using a chemical co-precipitation method. All synthetized nanoparticles were examined for shape, crystal structure and morphology/ microstructure using X-ray diffractometers, scanning electron microscopy and transmission electron microscopy. The hydrodynamic diameter and zeta-potential was measured by dynamic light scattering. Energy Dispersive Spectroscopy evaluated copper doping in zinc oxide nanoparticles. The anticancer effects were tested on bone cancer fibroblast cells and normal lung fibroblast cells using cell viability test, colony formation assay, and lactate dehydrogenase assay at concentrations of 0, 1, 10, 17.5, 25, 50, 100, and 200 μg/ml. In vivo experiments assessed serum markers (Aspartate aminotransferase, Alanine transaminase, blood urea nitrogen and creatinine) and liver malondialdehyde levels in response to 5 mg/kg and 50 mg/kg doses. Results zinc oxide nanoparticles exhibited a spherical morphology and good dispersion, with an average grain size ranging from 15–39 nm. Copper-doped zinc oxide nanoparticles displayed a mixture of rod-like and grain-like structures, and a larger average grain size of 18–68 nm. X-ray diffraction analysis confirmed the wurtzite crystal structure for both types of nanoparticles. While individual grain sizes varied, the mean particle size for all samples, including those with increasing copper doping, was approximately 100 ± 0.1 nm. Both nanoparticles exhibited a negative zeta potential. In vitro studies revealed that copper-doped zinc oxide nanoparticles, zinc oxide nanoparticles, and bulk zinc oxide exhibited cytotoxic activity (cell viability < 80%) and induced apoptosis in bone cancer fibroblast cells at 17.5 μg/ml after 72 h (P < 0.05). The copper-doped zinc oxide nanoparticles demonstrated higher cytotoxicity compared to zinc oxide nanoparticles and bulk zinc oxide at higher concentrations (P < 0.05). The copper-doped zinc oxide nanoparticles also showed significant inhibition of cell proliferation over 10 days at 17.5 μg/ml (P < 0.05). In vivo studies indicated no significant changes in serum Aspartate aminotransferase, Alanine transaminase, blood urea nitrogen, and creatinine levels at 5 mg/kg. However, a 50 mg/kg dose of zinc oxide nanoparticles and copper-doped zinc oxide nanoparticles significantly increased these serum markers and liver malondialdehyde levels (P < 0.05). Histological analysis revealed liver injury in rats treated with 50 mg/kg but not at 0.5 mg/kg. Conclusions The copper-doped zinc oxide nanoparticles exhibit enhanced cytotoxicity and anticancer activity compared to zinc oxide nanoparticles and bulk zinc oxide, particularly at higher concentrations. High doses of these nanoparticles could induce significant biochemical changes and liver injury in vivo, highlighting the need for careful dose management.